2017
DOI: 10.1089/pho.2016.4204
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Laser Photobiomodulation on Morphological and Functional Repair of the Facial Nerve

Abstract: LLLT enhanced axonal regeneration and accelerated functional recovery of the whiskers, and both repair techniques allowed the growth of axons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 51 publications
2
50
0
Order By: Relevance
“…With the evolution of the technology in the health field and the evolution of the adjunct methods for rehabilitation and functional restoration of injured nerves [3,6,7,8,9], the PBMT has shown a wide range of benefits with clinical relevance. Thus, the aim of this research was to carry out a review of the scientific papers published in the last 10 years in order to verify the relation of PBMT in the regeneration of injured peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With the evolution of the technology in the health field and the evolution of the adjunct methods for rehabilitation and functional restoration of injured nerves [3,6,7,8,9], the PBMT has shown a wide range of benefits with clinical relevance. Thus, the aim of this research was to carry out a review of the scientific papers published in the last 10 years in order to verify the relation of PBMT in the regeneration of injured peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The functional analysis evidenced the evolution of functional recovery associated with PBMT [6,7,34,38,39]. Marcolino et al [40] found a functional recovery with both 40 J/cm 2 and 80 J/cm 2 (830 nm), Akgul; Gulsoy; Gulcur [41] also scored improvement in functionality with late application PBMT (650 nm) (7 days after injury), as well as Medalha et al [35] at 660 nm at 50 J/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations